Individual cognitive style affects flood‐risk perception and mitigation intentions. Issue 3 (16th November 2020) - Spaccatini, Federica; Pancani, Luca; Richetin, Juliette; Riva, Paolo; Sacchi, Simona
Abstract: Risk perception of natural hazards has been widely studied as one of the potential determinants of people's behaviors and behavioral intentions. However, individual differences can also affect risk perception. The present work focused on the link between an individual cognitive mindset (i.e., level of holism) and flood‐risk perception. It also assessed the consequences of such a link on public and personal mitigation intentions, taking into account the sense of connection with the environment, the psychological distance from the adverse event, and the role played by previous personal experience with flooding. Our study ( N = 191) showed that the individual cognitive style predicted risk perceptions and personal (for both experienced and no‐experience groups) and public (only for experienced group) mitigation intentions, through the mediation of the sense of connection with the environment and the psychological distance from the adverse event. Results are discussed in terms of their practical implications for public communication and policies about environmental hazards.